Paul Henry Gerber — physician, professor and poet from Königsberg - Ilya О. Dementev (Слово.ру: балтийский акцент)
The article explores the biography of Professor Paul Henry Gerber (1863-1919), a bright representative of the intellectual elite of Königsberg at the turn of the 19th-20th centuries. A native of the capital of the German province East Prussia, he was an outstanding otorhinolaryngologist, a lecturer at the University of Königsberg, as well as an original poet and publicist. The study, based on biographical and narrative methods, reveals the main stages of Gerber’s life, and clarifies the dating of its most important events. The author comments the Gerber’s most significant works, including scholarly publications on Wolfgang Amadeus Mozart and Johann Wolfgang Goethe (the article briefly covers subsequent scholarly controversy surrounding the article on Mozart’s ear). Some of Gerber’s scholarly and popular texts are quoted, reflecting both his varied interests and the specificity of his literary style. Based on the materials of address books of Königsberg the article reconstructs the addresses of Gerber’s residence and work as well as the current state of the places connected with the biography of the outstanding citizen of Königsberg (the house where Gerber lived in the last years of his life has been preserved and included in the register of cultural heritage objects in contemporary Kaliningrad, but the memory of the famous tenant is not commemorated there). The author describes the research perspectives related to further study of the integration of medical and literary discourses.